Incommensurate magnetism in the coupled spin tetrahedra system Cu2Te2O5Cl2 - Zaharko, O.; Ronnow, ,H.M.; Daoud-Aladine, A.; Streule, S.; Juranyi, F.; Mesot, J.; Berger, H.; Brown, P.J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
Neutron scattering studies on powder and single crystals have provided new evidences for unconventional magnetism in Cu2Te2O5Cl2. The compound is built from tetrahedral clusters of S = 1/2 Cu2+ spins located on a tetragonal lattice. Magnetic ordering, emerging at TN = 18.2 K, leads to a very complex multi-domain, most likely degenerate, ground state, which is characterized by an incommensurate (ICM) wave vector k [0.15, 0.42, 1/2]. The Cu2+ ions carry a magnetic moment of 0.67(1) mB/Cu2+ at 1.5 K and form a four helices spin arrangement with two canted pairs within the tetrahedra. A domain redistribution is observed when a magnetic field is applied in the tetragonal plane (Hc ≈ 0.5 T), but not for H||c up to 4 T. The excitation spectrum is characterized by two well-defined modes, one completely dispersionless at 6 meV, the other strongly dispersing to a gap of 2 meV. The reason for such complex ground state and spin excitations may be geometrical frustration of the Cu2+ spins within the tetrahedra, intra- and inter-tetrahedral couplings having similar strengths and strong Dzyaloshinski–Moriya anisotropy. Candidates for the dominant intra- and inter-tetrahedral interactions are proposed.